Aktivitas fisik dan screen based activity pada remaja di Wates - Siti Nurfadilah H; Madarina Julia; Riris Andono Ahmad (Fakultas Kedokteran Universitas Gadjah Mada, 2017)
Physical activity and screen based activity with adolescent sleep patterns in Wates PurposeThe purpose of this study was to explore the relationship between physical activity and screen based activity with sleep patterns in adolescents.MethodsA cross-sectional study was conducted among junior high school students in August 2016. Samples were 536 respondents selected using stratified random sampling. Data were collected through interviews with a structured questionnaire, and measurements of height and waist circumference. Data analyses used chi-square, mann-whitney and logistic regression tests to explore factors associated with sleep pattern.ResultsOut off 536 respondents, poor sleep quality (34.5%) and short sleep duration (45.3%) happened among female adolescents. There was a significant correlation between screen based activity with sleep quality in adolescents. Physical activity had a significant relationship with sleep duration.ConclusionPhysical activity and SBA was associated with adolescent sleep patterns. Appropriate educational promotions by the Kulon Progo education authorities should be conducted to provide information about the importance of adequate sleep.